A Critical Review of Methane Trapping Mechanism to Optimize CBM Production. - Tunio, Saleem Qadir (Maxwell Science Publication, 2012)
Optimizing Coal Bed Methane (CBM) production depends on the trapping mechanism of methane in the micro pores of coal bed. Methane is trapped in coal beds by adsorption on the free surface. The free surface is mainly available as the micro pores and partly as different cleats. The average percentage of micro pores (1.2x10-7 cm diameter) in a coal increases with rank and ranges from 19.3% in lignites to 75% in anthracites. The effective molecular diameter of adsorbed methane is 4.1x10-8 cm suggesting a maximum of three molecules can be accommodated in a unit micro pore. The commitment of optimized production of methane depends on the amount adsorbed on the coal surface. Methane in the micro pore can be accommodated either by solution in pore water or adsorption or as free gas under pressure. If it is dissolved in water, then for CBM production it is not useful because the dissolved gas will be expelled during dewatering phase of the well completion. It is only the free gas and the adsorbed gas that need to be evaluated for optimized production. Langmuir assumed a mono-layer of adsorption in selective locales on the adsorbent whereas many of the present day models assumed multi-layers of adsorbates (BET: Stephen Brunauer, Paul Emmett and Edward Teller). Problem arises with the concept of layering during adsorption process whereby it is difficult to think of adsorption of methane over a methane layer. With higher pressure methane can be accommodated as free gas but will not be adsorbed on any methane surface. It is therefore necessary to understand how methane molecule is trapped in the micro pores of the coal bed in order to optimize the CBM production. Keywords: Adsorption, CBM, methane, trapping